Evaluation De La Qualité Microbiologique Des Médicaments Traditionnels Améliorés (MTA) Vendus Dans Six Communes d’Abidjan (Côte d’Ivoire) - Bakary, Coulibaly; Clément, Kouassi Kouassi; Ehoulé, Kroa; Ibrahim, Konaté; Elisée, Kouassi Kporou; Joseph, Djaman Allico (European Scientific Journal, ESJ, 2018)
This study was carried out in six (6) communes of Abidjan within a period of six months (November 2016 to April 2017). This paper focuses on assessing the microbiological quality of traditional medicines produced and sold in these communes. A total of 38 samples were collected, including 19 in powder form and another 19 in liquid form. The search and enumeration of the germs was carried out according to the method based on standard procedures (AFNOR). Enumeration included total mesophilic aerobic flora, total coliforms, yeasts and molds, Staphylococcus aureus, and salmonella. The results indicate an absence of the pathogenic flora (Salmonella and S. aureus). There is also an absence of yeasts and molds in the products in liquid form. The level of contamination of the Mesophilic Total Aerobic Flora (FMAT) ranges from 1.104 to 6.7.107 CFU / ml or CFU / g and from 1.6.104 to 5.5.107 CFU / g or CFU / ml for total coliforms. In terms of microbiological quality, 39.47% of the analyzed samples had compliant. In view of these results, it is necessary to train Traditional Medicine Practitioners on Good Manufacturing Practices (GMP) methods throughout the production chain in order to market MTAs of guaranteed quality and safety